Risk Analysis of CO and CO₂ Exposure Before and After Practicum - Widiyaristi, Dessy; Apriani, Gita; Fanessa, Tria Ivanda; Raihana, Jasmine (VISIKES, 2025)
Laboratory air quality is an important factor affecting the health of laboratory users. The Chemistry Department of FMIPA UNSRI consist of biochemistry, analytical chemistry, physical chemistry, organic chemistry, and inorganic chemistry laboratories. This study aimed to evaluate the potential hazards caused by exposure to carbon monoxide (CO) and carbon dioxide (CO2) among the laboratory users in the Chemistry Study Program at FMIPA UNSRI. This study was an observational study using the Environmental Health Risk Analysis (EHRA) method. Measurements were taken before and after the practicum. The study was conducted in 5 laboratories within the Chemistry Study Program at FMIPA UNSRI. The concentrations of CO and CO2 showed that the conditions after the practicum were higher than before the practicum, CO reached 2.07 ppm and CO2 reached 631.69 ppm with the risk quotient (RQ) for both CO and CO2 both showing RQ > 1. Based on the EHRA calculation, it shows that the accumulation of CO and CO2 gases after the practicum suggest that continuous exposure for 8 hours per day over 5 consecutive days may have adverse health effects on laboratory users, including lecturers, students and analysts at FMIPA environment. Therefore, it is recommended to implement risk management, monitoring and use Personal Protective Equipment (PPE) whenever entering the laboratory. Laboratory air quality is an important factor affecting the health of laboratory users. The Chemistry Department of FMIPA UNSRI consist of biochemistry, analytical chemistry, physical chemistry, organic chemistry, and inorganic chemistry laboratories. This study aimed to evaluate the potential hazards caused by exposure to carbon monoxide (CO) and carbon dioxide (CO2) among the laboratory users in the Chemistry Study Program at FMIPA UNSRI. This study was an observational study using the Environmental Health Risk Analysis (EHRA) method. Measurements were taken before and after the practicum. The study was conducted in 5 laboratories within the Chemistry Study Program at FMIPA UNSRI. The concentrations of CO and CO2 showed that the conditions after the practicum were higher than before the practicum, CO reached 2.07 ppm and CO2 reached 631.69 ppm with the risk quotient (RQ) for both CO and CO2 both showing RQ > 1. Based on the EHRA calculation, it shows that the accumulation of CO and CO2 gases after the practicum suggest that continuous exposure for 8 hours per day over 5 consecutive days may have adverse health effects on laboratory users, including lecturers, students and analysts at FMIPA environment. Therefore, it is recommended to implement risk management, monitoring and use Personal Protective Equipment (PPE) whenever entering the laboratory.